Dietary restriction modulates mitochondrial DNA damage and oxylipin profile in aged rats. (19th April 2022) - Gureev, Artem P.; Andrianova, Nadezda V.; Pevzner, Irina B.; Zorova, Ljubava D.; Chernyshova, Ekaterina V.; Sadovnikova, Irina S.; Chistyakov, Dmitry V.; Popkov, Vasily A.; Semenovich, Dmitry S.; Babenko, Valentina A.; Silachev, Denis N.; Zorov, Dmitry B.; et al.
Abstract : Age‐related impairment of coordination of the processes of maintaining mitochondrial homeostasis is associated with a decrease in the functionality of cells and leads to degenerative processes. mtDNA can be a marker of oxidative stress and tissue degeneration. However, the mechanism of accumulation of age‐related damage in mtDNA remains unclear. In the present study, we analyzed the accumulation of mtDNA damage in several organs of rats during aging and the possibility of reversing these alterations by dietary restriction (DR). We showed that mtDNA of brain compartments (with the exception of the cerebellum), along with kidney mtDNA, was the most susceptible to accumulation of age‐related damage, whereas liver, testis, and lung were the least susceptible organs. DR prevented age‐related accumulation of mtDNA damage in the cortex and led to its decrease in the lung and testis. Changes in mtDNA copy number and expression of genes involved in the regulation of mitochondrial biogenesis and mitophagy were also tissue‐specific. There was a tendency for an age‐related decrease in the copy number of mtDNA in the striatum and its increase in the kidney. DR promoted an increase in the amount of mtDNA in the cerebellum and hippocampus. mtDNA damage may be associated not only with the metabolic activity of organs, but also with the lipid composition and activity of processes associated with the isoprostanes pathway of lipid peroxidation. The comparison of polyunsaturated fatty acids and oxylipin profiles in old rats showed that DR decreased the synthesis of arachidonic acid and its metabolites synthesized by the cyclooxygenase, cytochrome P450 monooxygenases and lipoxygenase metabolic pathways. Abstract : Aging is associated with the accumulation of mtDNA damage, mtDNA copy number, suppression of mitochondrial biogenesis and mitophagy, and alterations in oxylipins profile. Here, we show that some organs (i.e. brain compartments, excluding the cerebellum, as well as the kidney) were more susceptible to age‐related damage than others (i.e. liver, testis and lung). We found that dietary restriction reversed these alterations via modulation of mtDNA damage and oxylipin profile.